2019
DOI: 10.1002/er.4565
|View full text |Cite
|
Sign up to set email alerts
|

Carbon conversion and stabilisation of date palm and high rate algal pond (microalgae) biomass through slow pyrolysis

Abstract: Summary The processing of waste through pyrolysis technology is gaining momentum worldwide and is considered to be a green technology to reduce CO2 emissions. This study is devoted to analysing the lignocellulosic biomass (date palm) and wastewater‐derived microalgae and the carbon‐rich char produced between temperature range (400°C‐600°C) from these biomass types. The properties of microalgae char showed that significant variation with date palm char exhibited high heating values (24‐28 MJ/kg), low ash conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 59 publications
(94 reference statements)
1
6
0
Order By: Relevance
“…Chiodo et al, 34 previously reported that algae char tend to show high O/C ratios than lignocellulosic biomass derived char when pyrolysed individually at all HTTs (400, 500 and 600 °C). This phenomenon also observed in a recent study by Akhtar et al, 24 for wastewater derived microalgae. Hence, a co-pyrolysis is a suitable approach to gain overall lower O/C ratio in the end product, and CT can further reduce the atomic ratio to increase the aromaticity of the char.…”
Section: Atomic Ratios and Van Krevelen Diagramsupporting
confidence: 86%
“…Chiodo et al, 34 previously reported that algae char tend to show high O/C ratios than lignocellulosic biomass derived char when pyrolysed individually at all HTTs (400, 500 and 600 °C). This phenomenon also observed in a recent study by Akhtar et al, 24 for wastewater derived microalgae. Hence, a co-pyrolysis is a suitable approach to gain overall lower O/C ratio in the end product, and CT can further reduce the atomic ratio to increase the aromaticity of the char.…”
Section: Atomic Ratios and Van Krevelen Diagramsupporting
confidence: 86%
“…N 2 was used as carrier gas (50 mL min À1 ). Furthermore, in order to analyze the specific pyrolysis mechanism, based on the TG data, the kinetic analysis was performed by Arrhenius equation combining with Coasts-Redfern method, [24][25][26] which can be described as follows:…”
Section: Characterization Of Bio-charmentioning
confidence: 99%
“…Wastewater derived microalgae (WWM) was collected from a wastewater treatment plant. The individual properties of each of the feedstock can be referred to Akhtar et al, 25 and Akhtar et al, 24 . The derived microalgae contained a number of species including Actinustrum sp., Coleastrum sp., Diatom sp., and Mucidosphaerium pulchellum.…”
Section: Pyrolysis Experimentsmentioning
confidence: 99%
“…Although co-pyrolysis of lignocellulosic biomass and microalgae showed an optimistic trend to improve the properties of bio-oil and gas, further studies are required for exclusive char production. In a recent study by Akhtar et al, 24 , microalgae biomass tend to produce less stable char than date palm biomass and have shown the presence of high nitrogen content leading to several types of nitrogen species found on the surface of the char. Congruently, the energy content was also lower as compared to date palm biomass.…”
Section: Introductionmentioning
confidence: 99%